Financial Report Data Processing System Input Vat And Output Vat: Case Study In Ahass Honda Andrew Motor - Julianus Waruwu; Rohmat Nur Ibrahim (Informatics Management, Engineering and Information System Journal, 2023)
Applying the right value-added tax calculation system can satisfy workers and agencies. Calculating input and output value-added tax often experiences problems in its calculation, which is still semi-EDP. The financial data processing system of input VAT and output VAT at Ahass Honda Andrew Motor is web-based with data collection techniques in the form of observation, interviews, and literature studies. It is designed with the OOAD system development method, namely the process of analyzing, designing, and implementing the system based on the object. The design of this system can make it easier for companies to input and calculate value-added tax input and output, facilitate the calculation process because it is done automatically, and facilitate the process of printing the final report to be more effective and efficient.